A comparative study on students' perception of . educational environment between a public and a private medical assistant college, Malaysia - Arzuman, Hafiza; Esa, Abd Rahman Esa; Chit, Som Phong A/L (Pusat Pengajian Sains Perubatan, Universiti Sains Maalaysia, 2011)
Introduction: A cross sectional comparative study which was descriptive in nature was carried out among the final year medical assistant students at Kolej Pembantu Perubatan Seremban(public) and Kolej Islam Sains dan Teknologi (private). The objective of the study was to measure and compare the students' perception of educational environment between a public and a private medical assistant college by using the Dundee Ready Educational Environment Measure (DREEM) inventory. The DREEM inventory is a validated global instrument for measuring educational environment in undergraduate medical and health professional education. Methodology: The Malay version of the DREEM inventory was administered to all the final year students (Public 149 + Private 69 = n 218) from both the colleges. Before administering the questionnaire the purpose, confidentiality and ethical issues were explained to the students. The ethical clearance was obtained from the research ethics committee of the School of Medical Sciences, USM Results: The overall response rate was 80.27% (175 /218) for both the colleges. The response rate from public college was 82.55% while in private it was 75.36%. Overall DREEM mean score for private was slightly higher 130.07/200 (17.70) compared to public was 128.91/200 (16.72). In all five Domains of DREEM the students of both the colleges had positive perceptions. The mean score is higher for 4 domains of private college whereas in domain 5 it was slightly higher for public college. However the scores indicated plenty of scope for improvement in all five Domains of educational environment of both the colleges. In public college 6/50 items scored >3, 39/50 items scored within 2-3 and 5/50 items scored <2. On the other hand private college 17/50 items scored >3, 27/50 items scored within 2-3 and 6/50 items scored <2. However in individual item analysis the private college is in slightly better position than public college. As per DREEM scoring scheme the students' perception of the educational environment of both the colleges were more positive than negative. Nevertheless, the study also revealed some problematic areas of the educational environment for both the colleges. Conclusion: The study concluded that the educational environment of the colleges was more positive. The private college scored slightly better in all aspects of the educational environment than public one. However there were few items scored <2 and need to be explore further for remedial measures. In terms of educational environment both the colleges had more or less similar findings. Therefore the study recommended that both the colleges should look each other's weak and strong areas, work together and take remedial measures to improve their educational environment. The small number of participants only from the final year was identified as one of the major limitations of the study.